METAFISIKA KEJADIAN DALAM PERSPEKTIF TEORI MOSEN - Bertha Wikara (Institut Teknologi Sepuluh Nopember, 2008)
Many incidents happen in the universe. They are make humans embittered and try to understand about them. Things about incident were searched in this research : how an incident emerge, actor of all incidents in universe, and formula that represents all incidents in universe and with the using of it. Inductive thinking by using datas which they are not results from an experiment was used as research method. The results of the research are : 1) An incident emerge because a movement, 2) Actor of all incidents in universe is mosen, 3) Formula that represents all incidents in universe is input = output. The formula called incident formula, 4) The using of incident formula is for the basic of zero change postulate making, which the postulate’s statement is, “ there is no change in each incident in universe. Change that happens is not real “, the incident formula is also used for the basic of mosen cycle postulate making, which the postulate’s statement is, “ each movement of mosen is a cycle ”. Point 1 to 3 plus zero change postulate called incident theory.